Advertisement of antibiotics for upper respiratory infections and equity in access to treatment: a cross-sectional study in Nepal - Pramesh Koju; Stéphane P. Rousseau; Marc Van der Putten; Archana Shrestha; Rajeev Shrestha (Taylor & Francis Group, 2020)
Background Pharmaceutical companies actively advertise their branded antibiotics, which influence their sales at community pharmacies. The major proportion of out of pocket health spending is on medicine; and affordability of antibiotics has always been a crucial issue in most developing countries. This study identified promotional activities adopted by pharmaceutical companies in community pharmacies and medicine shops and the affordability of selected antibiotics to clients with lowest wages in Kavrepalanchok district of Nepal. Methods A cross-sectional study was conducted among all community pharmacies and medicine shops (n = 34) in Dhulikhel and Banepa. Available pharmacists / personnel were interviewed, using a structured questionnaire, on the characteristics of the pharmacies, promotional activities, and sales and prices of antibiotics used to treat acute upper respiratory tract infections. This study looked at the association of promotional activities (financial bonus, free samples, and books/brochure/gifts) with the type of antibiotics. Further, affordability was assessed of the most popular antibiotics by comparing the total treatment cost against the lowest wage for unskilled workers in Nepal. Results Financial bonus, free samples, and brochures were the most popular promotional activities. It is also noticed that antibiotics which are top selling were those with a high number of promotional activities. Amoxicillin, azithromycin and amoxicillin+clavulanate had 42, 29 and 17 promotional activities respectively. Irrespective of the prices of antibiotics, almost all of the most popular antibiotics for acute upper respiratory infections were unaffordable for unskilled workers costing them more than a day's wage. Conclusions Upper respiratory tract antibiotics are widely promoted at community pharmacies. The treatment cost of antibiotics is unaffordable for unskilled workers in Nepal irrespective of the type and unit cost of antibiotics.